A comparison of serum and transcutaneous methods for diagnosis of neonatal hyperbilirubinemia - Hesaraki, Mehran (International Journal of Research in Medical Sciences, 2017)
Background: Bili-Check is a simple test for non-invasive, quick, and painless estimation of the total serum bilirubin. This research aimed to compare serum and transcutaneous methods for the diagnosis of neonatal hyperbilirubinemia. Methods: In this descriptive study, a sample of 120 neonates diagnosed with hyperbilirubinemia was selected using convenience non-probability. They were hospitalized in Amir Al-Momemin Hospital of Zabol, Iran in 2013. The extent of neonatal bilirubin was measured by NINGBO DAVID and lab test. Then, they were compared. The data were analyzed using correlation and t-test in SPSS 22. Results: In this descriptive study, a sample of 120 neonates diagnosed with hyperbilirubinemia was selected using convenience non-probability. They were hospitalized in Amir Al-Momemin Hospital of Zabol, Iran in 2013. The extent of neonatal bilirubin was measured by NINGBO DAVID and lab test. Then, they were compared. The data were analysed using correlation and t-test in SPSS 22. Conclusions: The results showed that Bili-Check can be recommended as an appropriate tool for screening and monitoring phototherapy process. The serum method can be replaced by Bili-check.